THE CORRELATION AMONG NURSING KNOWLEDGE, TRAINING ON SDKI, SIKI AND SLKI WITH THE QUALITY OF NURSING CARE DOCUMENTATION IN HOSPITAL INPATIENT ROOMS - Wiwin Sulistyawati; Susmiati , Susmiati (UNEJ e-Proceeding, 2020)
Nursing documentation is an essential part of administrative activities as a guarantee of services provided to patients. Public awareness of her rights demands that the nursing profession work professionally and document its nursing care well. Incomplete documentation can degrade the quality of nursing services. The varying understanding of nursing care arrangements contributes to the quality of nursing care documentation. This research aims to find out the relationship between nurse knowledge and nurse training on SDKI, SIKI, and SLKI and the quality of nursing care documentation in hospital inpatient rooms. This method of research is a correlative descriptive with a cross-sectional design. In this study, the samples were nurses in the inpatient room who had implemented SDKI, SIKI, and SLKI; 84 respondents were taken by consecutive sampling. Research instruments in the form of questionnaires sent using google form. Analyze data using the Chi-Square test. The results showed there is a relationship of nurse knowledge about SDKI, SIKI, and SLKI with the quality of nursing care documentation (p-value: 0.001< α: 0.005), and there is a relationship of training about SDKI, SIKI, and SLKI with the quality of nursing care documentation (p-value: 0.000< α: 0.005). This study of nurse knowledge and training on good SDKI, SIKI, and SLKI make nursing care documentation useful. Based on the study, the Head of Nursing Division needs to conduct training about SDKI, SIKI, and SLKI to improve nurse knowledge and the quality of nursing documentation that will later impact the quality of nursing services. Keywords: Understanding nurses; Training on SDKI, SIKI, SLKI; documentation; nursing care.